Polymeric hyaluronic acid structure, its manufacturing method and eye drop composition containing the same
By applying shear stress to polymeric hyaluronic acid to form single polymer chains with intramolecular interactions, the viscosity of eye drop compositions is reduced, addressing the irritation and stickiness issues associated with high molecular weight hyaluronic acid while preserving its beneficial properties.
Patent Information
- Application Number
- JP2024549529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2023-02-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-02-17
AI Technical Summary
Conventional eye drops with high molecular weight hyaluronic acid often have high viscosity, which while effective in relieving dry eye symptoms, can irritate the eyeballs and cause stickiness or dryness upon blinking, leading to blurred vision.
A structure of polymeric hyaluronic acid with reduced viscosity is achieved by applying shear stress to the polymer chains, transforming them from a pair of twin helix structures into a single polymer chain with intramolecular interactions such as ionic bonds and ion clusters, without reducing the molecular weight.
The resulting eye drop composition maintains the moisture retention and epithelial regeneration abilities of high molecular weight hyaluronic acid while significantly reducing viscosity, improving the feel of use and eliminating stickiness upon application.
Smart Images

Figure 2025507431000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0023811 dated February 23, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a polymeric hyaluronic acid structure, a method for producing the same, and an eye drop composition containing the same, and more particularly to a polymeric hyaluronic acid structure in which the viscosity is reduced by applying shear stress to the polymeric hyaluronic acid, a method for producing the same, and an eye drop composition containing the same. [Background technology]
[0003] Dry eye is a condition in which the tear gland is dysfunctional, causing less tear production and more tear evaporation, resulting in dry eyes. This is a phenomenon in which the tear film dries out, and is accompanied by increased osmotic pressure and inflammation of the ocular surface. It is a disease that can cause inconvenience in daily life and, in severe cases, can even lead to blindness.
[0004] Eye drops are the most commonly used treatment for dry eye, and commercially available eye drops have been developed with a focus on replenishing the aqueous layer, which is the middle layer of tears, and preventing water from evaporating through polymeric substances, such as hyaluronic acid, carboxymethylcellulose (CMC), hydropropylmethylcellulose (HPMC), polyvinyl alcohol (PVA), etc.
[0005] Of these polymeric substances, hyaluronic acid is a biopolymer present in the human body, and is abundantly distributed in the skin, vitreous body of the eye, synovial fluid, muscle, umbilical cord, cockscomb, etc., and performs various functions in various parts of the body. Hyaluronic acid is also highly soluble in water, making it easy to develop into eye drops, and hyaluronic acid eye drops account for approximately 70% of the artificial tears market.
[0006] Eye drops that contain hyaluronic acid as a main ingredient on the market contain hyaluronic acid at concentrations of 0.1%, 0.15%, 0.18%, and 0.3%, and generally products with low concentrations are commercially available.
[0007] Hyaluronic acid has different viscosity depending on molecular weight even at the same concentration, and the higher the molecular weight of hyaluronic acid, the higher the viscosity. However, in the case of conventional eye drops containing hyaluronic acid, if the viscosity of the eye drops is high, it has a large symptom relief effect, but it also has problems such as irritation to the eyeball of dry eye patients, stickiness and dryness when blinking, and blurred vision.
[0008] There is an increasing demand for eye drops in which hyaluronic acid is added at a high concentration or which contain high molecular weight hyaluronic acid at the same concentration and have an adjusted viscosity. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Publication No. 2021-0015377 (2021.02.10), Method for producing low-viscosity hyaluronic acid Summary of the Invention [Problem to be solved by the invention]
[0010] The technical problem to be solved by the present invention is to provide a polymeric hyaluronic acid structure, a method for producing the same, and an eye drop composition containing the same, and more specifically, to provide a polymeric hyaluronic acid structure having a reduced viscosity without reducing the molecular weight by applying shear stress to the polymeric hyaluronic acid, a method for producing the same, and an eye drop composition containing the same.
[0011] The technical problems that the present invention aims to achieve are not limited to the technical problems mentioned above, and other technical problems not mentioned above will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from the following description. [Means for solving the problem]
[0012] In order to achieve the above technical objective, the viscosity of a solution containing a polymeric hyaluronic acid structure according to one embodiment of the present invention may be 1 to 60 cP.
[0013] In one embodiment of the present invention, the molecular weight of the hyaluronic acid is 5.0×10 5 ~2.0×10 6 It may be in the g / mol range.
[0014] In one embodiment of the present invention, the solution containing the structure may contain hyaluronic acid in a content of 0.01% (w / v) to 0.5% (w / v).
[0015] In one embodiment of the present invention, when the molecular weight and concentration of the structure and the hyaluronic acid that is the precursor of the structure are the same, the ratio of the viscosity (a) of the solution containing the structure to the viscosity (b) of the solution containing the hyaluronic acid that is the precursor of the structure, a / b, may be 0.001 to 0.30.
[0016] In one embodiment of the present invention, the intrinsic viscosity of the solution containing the structure is 0.1 to 2.5 m 3 / kg.
[0017] The present invention can provide an eye drop composition containing the above-mentioned polymeric hyaluronic acid structure.
[0018] In one embodiment of the present invention, the viscosity of the eye drop composition may be 1.0 to 30.0 cP.
[0019] In one embodiment of the present invention, the eye drop composition may further comprise an excipient.
[0020] In one embodiment of the present invention, the excipient may be at least one selected from the group consisting of a buffer, a preservative, a tonicity adjusting agent, and a pH adjusting agent.
[0021] The present invention can provide an eye drop composition for preventing or treating dry eye, comprising the above-mentioned eye drop composition.
[0022] The present invention can provide a kit comprising a container containing the eye drop composition, the container comprising a dispensing means suitable for topical administration of the eye drop composition.
[0023] In one embodiment of the present invention, the dispensing means may provide the eye drop composition dropwise in the form of drops having a volume of 0.01 to 0.10 ml. Effect of the Invention
[0024] The present invention has the advantage that the viscosity is significantly reduced and the feeling of use is improved by producing a new structure of hyaluronic acid structure that utilizes intramolecular interactions such as ionic bonds such as hydrogen bonds and / or interactions such as ion clusters while maintaining the same high molecular weight.
[0025] Furthermore, the eye drop composition containing the polymeric hyaluronic acid structure of the present invention has the advantage that it contains a large amount of hyaluronic acid and has improved moisture retention ability. [Brief description of the drawings]
[0026] [Figure 1] FIG. 2 is a diagram showing a polymer chain of hyaluronic acid, which is a precursor of a structure according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing a single polymer chain of hyaluronic acid, which is a precursor of a structure according to one embodiment of the present invention. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of an aqueous solution including a structure according to an embodiment of the present invention; [Figure 4] 1 is a scanning electron microscope (SEM) photograph of an aqueous solution including a structure according to an embodiment of the present invention; [Diagram 5] 1 is a transmission electron microscope (TEM) photograph of hyaluronic acid, which is a precursor of a structure according to an embodiment of the present invention. [Figure 6] FIG. 1 is a diagram showing a comparison of HPLC measurement results according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Generally, polymers have a long chain structure with regular repeating units formed by chemical reactions of monomer molecules, unlike the structure of molecules with low molecular weight. The structure of polymers with long chains exists in a solid state, or has a twisted chain structure when in a liquid state.
[0028] In very dilute polymer solutions, the viscosity is related to the volume, which is well known from Einstein's equation and can be shown as follows:
number
[0029] The volume of a polymer solution per unit mass is larger as the molecular weight is larger, as the affinity between the solvent and the polymer is larger, and as the repulsive force between unit chain structures is larger.
[0030] Furthermore, when the concentration of a polymer solution is high, the chains penetrate each other and form a very large continuous structure, whereas when the concentration of the polymer is low, the interaction between the chains decreases.
[0031] Unlike ionic polymers, each chain of which exists independently, hyaluronic acid polymers in aqueous solution are known to form twin helix structures in which two chains are bundled together. This is sometimes called twin helix or macromolecular crowding. Figure 1 shows a schematic diagram of two chains of hyaluronic acid polymers intertwined with each other to form a twin helix structure.
[0032] In general, eye drops containing high molecular weight hyaluronic acid promote collagen synthesis, have a longer retention time in eyeball, and have excellent moisture retention effect compared with eye drops containing low molecular weight hyaluronic acid.However, there is a problem that after high molecular weight hyaluronic acid is applied to eyeball, it is sticky when blinking, and the feeling of use is poor.In order to solve these problems, many studies are being conducted to adjust the viscosity of polymer solution.
[0033] However, such viscosity control methods have limitations in that they do not maintain the polymer characteristics of hyaluronic acid, such as reducing the viscosity of the polymer solution by inducing hydrolysis of the polymer chain of hyaluronic acid through pH control, addition of a catalyst, etc., thereby reducing the molecular weight.
[0034] In order to solve the above problems, the present inventors have confirmed that a pair of polymer chains of a polymeric hyaluronic acid having a very high viscosity is converted into a single helix structure by applying a high shear stress, and an ion association is formed due to intramolecular interactions and / or interactions such as ion clusters between the single polymer chains.
[0035] This resulted in a decrease in the volume of the polymeric hyaluronic acid chains, which in turn reduced the volume of the polymeric hyaluronic acid in solution, thereby significantly reducing the viscosity.
[0036] In the following, first, a method for producing a polymeric hyaluronic acid structure according to one embodiment of the present invention will be described, and then the polymeric hyaluronic acid structure will be specifically described.
[0037] Method for producing polymeric hyaluronic acid structures The term "polymeric hyaluronic acid structure" as used herein means a structure having a single polymer chain structure formed by applying shear stress to polymeric hyaluronic acid having a pair of polymer chain structures.
[0038] The term "precursor" as used herein refers to a precursor or precursor used to generate the polymeric hyaluronic acid structure according to the present invention, i.e., the precursor of the polymeric hyaluronic acid structure according to the present invention refers to hyaluronic acid having a paired polymer chain structure to which no shear stress is applied.
[0039] The polymeric hyaluronic acid structure according to an embodiment of the present invention can be prepared by applying shear stress to a solution containing hyaluronic acid, which is a precursor of the structure.
[0040] The shear stress applied to the solution containing hyaluronic acid, which is the precursor of the structure, may be either mechanical shear stress or ultrasonic application.
[0041] The mechanical shear stress can be applied by attaching the solution containing hyaluronic acid, which is the precursor of the structure, to the inlet of a high-pressure disperser and dispersing it under high pressure.In addition, the solution containing hyaluronic acid, which is the precursor of the structure, can be injected into a mill such as a ball mill, pin mill, roll mill, etc., and mechanical shear stress can be applied.Hereinafter, mechanical shear stress will be specifically explained.When the solution containing hyaluronic acid, which is the precursor, passes through the nozzle of a high-pressure disperser at high speed, the hyaluronic acid, which is the precursor of the structure, is subjected to very high shear stress by passing through a physically narrow area.
[0042] The shear stress may be applied by using ultrasonic waves. The application of ultrasonic waves will be specifically described below.
[0043] According to one embodiment of the present invention, the shear stress may be applied by applying ultrasonic waves to a solution containing the hyaluronic acid.
[0044] When the ultrasonic waves are applied to a solution containing the hyaluronic acid, pressure waves are generated, and the pressure waves can apply shear stress to the hyaluronic acid, which is the precursor of the structure.
[0045] The intensity of the applied ultrasonic waves may be 200 J / sec to 800 J / sec or 400 J / sec to 600 J / sec.
[0046] The energy applied per volume of the applied ultrasound can be calculated by ultrasound intensity (J / sec) x application time (sec) / measurement volume (ml).
[0047] According to one embodiment of the present invention, the energy of the ultrasonic waves applied to the solution containing hyaluronic acid per volume may be 100J / ml to 90kJ / ml. If the energy of the ultrasonic waves is less than 100J / ml, sufficient shear stress is not applied to the solution containing hyaluronic acid, and it may be difficult to form a structure. If the energy of the ultrasonic waves exceeds 90kJ / ml, excessive heat is applied to the solution containing hyaluronic acid, and it may be difficult to form a structure.
[0048] The ultrasonic wave can be applied at 10°C to 80°C for 10 seconds to 500 minutes. When the ultrasonic wave is applied at a temperature below 10°C, the solution containing hyaluronic acid does not change, and when the ultrasonic wave is applied at a temperature above 80°C, a phase change occurs in the solution containing hyaluronic acid, which may make it difficult to form the polymeric hyaluronic acid structure according to the present invention. In addition, when the ultrasonic wave is applied for less than 10 seconds, the solution containing hyaluronic acid does not change, and when the ultrasonic wave is applied for a time exceeding 500 minutes, the structure in the solution containing hyaluronic acid is deformed, making it impossible to form the polymeric hyaluronic acid structure according to the present invention.
[0049] Polymeric hyaluronic acid structure The polymeric hyaluronic acid structure of the present invention can be produced by the above-mentioned production method. Specifically, the polymeric hyaluronic acid structure can be produced by applying shear stress to the precursor hyaluronic acid of the structure to form a single polymer chain.
[0050] The single polymer chain may have a structure that includes the chemical structure of hyaluronic acid as shown in FIG. 2. The chemical structure of hyaluronic acid includes one carboxyl anion (-COO) for every two cyclic hexoses. - ) groups.
[0051] The distance between the single polymer chains becomes short, and an ionic aggregate can be formed by intramolecular interaction and / or interaction such as ion cluster. The intramolecular interaction can be performed via intramolecular hydrogen bond, ionic bond, etc. The interaction such as ion cluster can be performed by carboxyl anion (-COO δ- ) and sodium cation (Na δ+ This can be achieved through interactions between the partial charges of
[0052] The ion associate can include a spherical structure as shown in Figures 3 and 4. The ion associate can have a spherical structure having a diameter of 1 to 20 nm, 2 to 18 nm, or 3 to 16 nm due to the intramolecular interaction or the interaction such as an ion cluster.
[0053] On the other hand, hyaluronic acid, which is a precursor of the structure according to the present invention, has a general polymer chain structure and does not contain ion associates having a spherical structure. Figure 5 is a TEM photograph of hyaluronic acid, which is a precursor of the structure according to the present invention, in which only lines are observed as traces generated during the freezing process for TEM photography of the hyaluronic acid, and the shape of ion associates having a spherical structure is not observed.
[0054] Molecular weight of polymeric hyaluronic acid structures The molecular weight of the polymeric hyaluronic acid structure according to the present invention is 5.0×10 5 ~2.0×10 6 g / mol, 5.5×10 5 ~1.95×10 6 g / mol, or 6.0 × 10 5 ~1.90×10 6 It may also be g / mol.
[0055] The molecular weight of the polymeric hyaluronic acid structure according to the present invention is the same as that of the precursor hyaluronic acid of said structure.That is, even if shear stress is applied to the solution containing the precursor hyaluronic acid of said structure to produce the polymeric hyaluronic acid structure, it can produce a structure that maintains the same molecular weight as the precursor hyaluronic acid of said structure before shear stress is applied, and has low viscosity.
[0056] In FIG. 6, (a) is a graph showing a molecular weight measurement curve of hyaluronic acid sodium salt, which is a precursor of the structure according to the present invention, and (b) is a graph showing a molecular weight measurement curve of the polymer hyaluronic acid structure according to the present invention.
[0057] As shown in Fig. 6, it was confirmed that the molecular weight measurement curve of the hyaluronic acid precursor of the structure according to the present invention and the molecular weight measurement curve of the polymeric hyaluronic acid structure according to the present invention are almost the same without any change.Therefore, the polymeric hyaluronic acid structure according to the present invention can provide a polymeric hyaluronic acid structure with reduced viscosity without reducing the molecular weight even when shear stress is applied to the hyaluronic acid precursor of the structure.
[0058] The polymeric hyaluronic acid structure according to the present invention maintains the characteristics of high molecular weight hyaluronic acid, such as moisture retention and excellent epithelial regeneration ability, while lowering the viscosity to eliminate stickiness when applied to the eyeball, improving the feel when used, and improving moisture retention.
[0059] Viscosity of polymeric hyaluronic acid structures 5.0×10 5 ~2.0×10 6 The viscosity of a solution containing a polymeric hyaluronic acid structure having a molecular weight of g / mol and a concentration of 0.1 to 0.5% may be 1 to 60 cP.
[0060] According to one embodiment of the present invention, when shear stress is applied to a solution containing polymeric hyaluronic acid, which is a precursor of the polymeric hyaluronic acid structure, the physical structure of the hyaluronic acid is transformed from a twin helix structure to a single polymer chain, thereby reducing the viscosity and maintaining the high molecular weight of the hyaluronic acid.
[0061] The reason why the viscosity of the solution containing the polymeric hyaluronic acid structure according to the present invention is significantly reduced is that the application of shear stress to the solution containing hyaluronic acid, which is the precursor of the structure, results in the formation of the single polymer chain, and the formation of ionic associations within the single polymer chain, thereby reducing the volume of the polymer chain, and thus reducing the volume of the polymeric hyaluronic acid in the solution.
[0062] According to one embodiment of the present invention, when the molecular weight and concentration of the polymeric hyaluronic acid structure and the hyaluronic acid precursor of the structure are the same, the ratio of the viscosity (a) of the solution containing the structure to the viscosity (b) of the solution containing the hyaluronic acid precursor of the structure, a / b, may be 0.001 to 0.30.
[0063] Contact angle of polymeric hyaluronic acid structures The contact angle of a solution containing the polymeric hyaluronic acid structure produced according to one embodiment of the present invention may be 20° to 30° on a hydrophilic glass surface, and 80° to 100° on a hydrophobic glass surface.
[0064] The contact angle may be measured by the sessile drop method for measuring a static contact angle, or the tilting drop method, captive drop method, Wilhelmy plate method, or the like for measuring a dynamic contact angle, and preferably by the sessile drop method.
[0065] The hydrophilic glass surface may be a glass surface containing an untreated silica material.
[0066] The hydrophobic glass surface may be a glass surface comprising a material coated with a Teflon emulsion.
[0067] Intrinsic viscosity of polymeric hyaluronic acid structures Intrinsic viscosity refers to the volume per unit mass of a polymer in the absence of viscous effects in the polymer solution.
[0068] The intrinsic viscosity can be measured by measuring the aqueous solution to be measured according to the concentration, calculating the reduced viscosity, and extrapolating the reduced viscosity at a concentration of 0. The intrinsic viscosity can be calculated using the following Equation 4.
[0069] The following formula 2 is a formula for calculating the relative viscosity, and the following formula 3 is a formula for calculating the reduced viscosity (where η is the viscosity of the solution, η0 is the viscosity of the solvent, and c is the concentration of the solution). Generally, the concentration (c) of the solution is expressed in units of (w / v), which means that η red This is because the physical meaning of is the volume per unit weight of the polymer in the solution. The reduced viscosity is plotted against the concentration, and the intercept obtained by linearly extrapolating the point where the concentration is 0 as described above is the intrinsic viscosity.
[0070]
number
[0071]
number
[0072]
number
[0073] The intrinsic viscosity of the solution containing the polymeric hyaluronic acid structure according to the present invention can be calculated based on the above-mentioned formulas 2 to 4. Specific intrinsic viscosity measurements of the solution containing the polymeric hyaluronic acid structure according to the present invention are described in the following Experimental Example 8.
[0074] Ophthalmic composition containing polymeric hyaluronic acid structure According to one embodiment of the present invention, there is provided an eye drop composition comprising the polymeric hyaluronic acid structure.
[0075] The eye drop composition can have the characteristics of the polymeric hyaluronic acid structure according to the present invention as is.
[0076] The explanation of the structure of the polymeric hyaluronic acid is the same as that described above. Ophthalmic compositions according to the invention may also contain other conventional ingredients such as one or more pharma- ceutically acceptable buffers, preservatives, tonicity adjusting agents, pH adjusting agents, and the like. The lower limit of the pH of the eye drop composition according to one embodiment of the present invention is preferably 5.5, more preferably 6, and even more preferably more than 6, and the upper limit is preferably 8, more preferably 7.5, and even more preferably 7. When the pH is within this range, the hyaluronic acid or a salt thereof in the eye drop composition is stabilized, and the eye drop composition is suitable for use as a low-irritant eye drop composition.
[0077] The eye drop composition according to one embodiment of the present invention may further include a buffer suitable for maintaining the above-mentioned preferred pH range. Examples of the buffer include, but are not limited to, bicarbonate buffer, acetate buffer, citrate buffer, phosphate buffer, borate buffer, or tromethamine (TRIS, 2-amino 2-hydroxymethyl-1,3-propanediol) buffer, and combinations thereof. The amount (concentration) of the buffer to be added is not particularly limited as long as the pH of the eye drop composition according to one embodiment of the present invention can be maintained within the above-mentioned preferred range.
[0078] The eye drop composition according to one embodiment of the present invention may further comprise a preservative suitable for preventing microbial contamination. The preservative may comprise any compound or substance. Examples of the preservative may be selected from the group consisting of persalts such as perborate, percarbonate, etc.; alcohols such as benzyl alcohol, chlorobutanol, etc.; preservatives containing quaternary ammonium salts such as benzalkonium chloride, benzalkonium bromide, polyquaterniums; guanidine-based preservatives including polyhexamethylene biguanidine (PHMB), chlorhexidine, etc.; mercurial preservatives such as thimerosal, phenylmercuric acetate, and phenylmercuric nitrate; metal subchlorides such as alkali and alkaline earth metal chlorites; ophthalmically acceptable salts such as sorbic acid and potassium sorbate and mixtures; and oxidative preservatives such as stabilized oxychloro complexes (e.g., Purite (registered trademark of Allergan, Inc.)). The amount of preservative may vary within a relatively wide range depending on the particular preservative used. If no preservative is added to the eye drop composition, the eye drop composition can be used as a single-use eye drop, where the eye drop composition is consumed after one administration. Otherwise, the eye drop composition can be used as a multi-use eye drop, for example, contained in a container with a filter attached to the nozzle of the container or contained in an airless application system device to dispense the eye drop.
[0079] The eye drop composition according to one embodiment of the present invention may further include a tonicity adjusting agent that adjusts the osmotic pressure of the eye drop to be similar to that in the eyeball and plays a role in eliminating irritation and pain caused by the osmotic pressure difference when the eye drop is administered. Examples of the tonicity adjusting agent may be in ionic and / or non-ionic form. Ionic tonicity adjusting agents are, for example, any one or more of the following alkali metal or earth metal halides: calcium chloride, potassium chloride, sodium chloride, lithium chloride, potassium bromide, sodium bromide, sodium iodide, sodium phosphate, potassium phosphate, sodium and potassium sulfate, sodium and potassium bicarbonate, and boric acid. Non-ionic tonicity adjusting agents are, for example, urea, glycerol, sorbitol, mannitol, propylene glycol, dextrose, or combinations thereof. Glycerin, sodium chloride, and mannitol are the most preferred tonicity adjusting agents. The amount of tonicity adjusting agent may vary depending on whether an isotonic, hypertonic, or hypotonic liquid is required. The composition of the present invention generally has an osmotic pressure in the range of 150 to 1500 mOsm / kg, preferably 150 to 500 mOsm / kg, and most preferably 180 to 250 mOsm / kg.
[0080] The eye drop composition according to one embodiment of the present invention may further contain a pH regulator to adjust the pH to the preferred range. The pH regulator is not particularly limited as long as it can adjust the pH of the eye drop composition according to one embodiment of the present invention, and specific examples include dilute hydrochloric acid, sodium hydroxide, etc. The amount (concentration) of the pH regulator added is not particularly limited as long as it can adjust the pH of the eye drop composition according to one embodiment of the present invention to the preferred range.
[0081] An eye drop composition according to one embodiment of the present invention can be prepared by dissolving the ingredients in an aqueous medium. Deionized water is a preferred aqueous medium which may contain small amounts of other hydrophilic solvents such as glycols and / or polyols. The composition can be prepared by preparing a solution of one or more ingredients and then adding the remaining one or more ingredients, or by preparing two or more separate solutions each containing one or more ingredients and then mixing all of the solutions together.
[0082] The eye drop composition according to one embodiment of the present invention may be an eye drop composition for preventing or treating dry eye.
[0083] The present invention provides a kit including a container containing the eye drop composition. The container containing the eye drop composition includes a dispensing means suitable for topically administering the eye drop composition to a patient's eye. The dispensing means can dispense the eye drop composition dropwise in a volume of 0.01 to 0.10 ml, but is not limited to this volume and can generally include a volume per drop to be applied to the eye. EXAMPLES
[0084] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments set forth herein.
[0085] Fabrication of polymeric hyaluronic acid structures [Example 1] Molecular weight is 9.0 x 10 5 0.5 g of sodium hyaluronate (Shiseido Co., Ltd.) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.5% (w / v).
[0086] The prepared hyaluronic acid sodium salt aqueous solution was placed in the inlet of a high pressure disperser (NLM 100 from ILSHIN AUTOCLAVE) and dispersed under high pressure, and then stabilized at room temperature for 1 hour to prepare an aqueous solution containing a polymeric hyaluronic acid structure.
[0087] [Example 2] An aqueous solution containing a polymeric hyaluronic acid structure was prepared in the same manner as in Example 1, except that the aqueous solution of hyaluronic acid sodium salt prepared in Example 1 was subjected to high pressure dispersion using a high pressure disperser two and three times.
[0088] [Example 3] Molecular weight is 1.2 x 10 6 An aqueous solution containing a polymeric hyaluronic acid structure was prepared in the same manner as in Example 1, except that 0.5 g of sodium hyaluronate (Shiseido Co., Ltd.) was used.
[0089] [Example 4] Aqueous solutions containing polymeric hyaluronic acid structures were prepared in the same manner as in Example 2, except that the aqueous solution of hyaluronic acid sodium salt prepared in Example 3 was subjected to high pressure dispersion using a high pressure disperser two, three and four times.
[0090] [Example 5] Molecular weight is 9.0 x 10 5 0.3 g of sodium hyaluronate (Shiseido Co., Ltd.) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.3% (w / v).
[0091] The aqueous solution of sodium hyaluronic acid prepared above was subjected to ultrasonic waves for about 20 minutes at 25°C using an ultrasonic homogenizer (HD4200, BANDELIN, Germany) to prepare an aqueous solution containing a polymeric hyaluronic acid structure. The total energy of the applied ultrasonic waves varied depending on the time, and about 1.5 kJ to 2.5 kJ of energy was applied per minute.
[0092] [Comparative Example 1] Molecular weight is 9.0 x 10 5 0.5 g of sodium hyaluronate (Shiseido Co., Ltd.) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.5% (w / v).
[0093] [Comparative Example 2] Molecular weight is 1.2 x 10 6 0.5 g of sodium hyaluronate (Shiseido Co., Ltd.) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.5% (w / v).
[0094] Experimental Example 1: Viscosity Comparison of Examples 1 to 4 and Comparative Examples 1 and 2 The viscosities of the aqueous solutions of Examples 1 to 4 and Comparative Examples 1 and 2 were measured at 25°C using a viscometer (Brookfield DV2T viscometer). The measured viscosities are shown in Tables 1 and 2 below. The aqueous solutions prepared in Example 2 by repeating high pressure dispersion using a high pressure disperser two and three times are shown in Examples 2-1 and 2-2, respectively. Additionally, the aqueous solutions prepared in Example 4 by repeating high pressure dispersion using a high pressure disperser two, three and four times are shown in Examples 4-1, 4-2 and 4-3, respectively.
[0095] [Table 1]
[0096] [Table 2]
[0097] From the results in Table 1, it was confirmed that the viscosity of the aqueous solution containing the polymeric hyaluronic acid structure prepared in Examples 1 and 2 was obviously lower than the viscosity of the sodium hyaluronic acid solution, which is the precursor of the structure prepared in Comparative Example 1. It was also confirmed that the viscosity decreased to about 10 cP by repeating the high pressure dispersion several times.
[0098] From the results in Table 2, it was confirmed that the viscosity of the aqueous solution containing the polymeric hyaluronic acid structure prepared in Examples 3 and 4 was significantly lower than the viscosity of the sodium hyaluronic acid solution, which is the precursor of the structure, prepared in Comparative Example 2. It was also confirmed that the viscosity decreased to about 10 cP by repeating high pressure dispersion several times.
[0099] It was found that when a specific shear stress is applied to the precursor sodium hyaluronic acid, the twin helix structure of hyaluronic acid is converted to a single helix structure, and a polymeric hyaluronic acid structure is produced in which ionic aggregates are formed within the single polymer chain. The reason why the viscosity of the solution containing the polymeric hyaluronic acid structure according to the present invention is significantly reduced is that the volume of the polymer chain can be reduced by forming ionic aggregates within the single polymer chain, and thus the volume of the polymeric hyaluronic acid in the solution is reduced.
[0100] Therefore, even if a high molecular weight hyaluronic acid is contained, a solution with reduced viscosity can be produced without changing the molecular weight.
[0101] Experimental Example 2: Change in viscosity depending on ultrasonic application time The viscosity of the aqueous solution containing the polymeric hyaluronic acid structure prepared in Example 5 was measured. The change in viscosity of the aqueous solution depending on the ultrasonic application time is shown in Table 3 below.
[0102] [Table 3]
[0103] From the results in Table 3, it was confirmed that when ultrasonic waves were applied to the aqueous solution containing the precursor polymeric hyaluronic acid in Example 5, the viscosity decreased as the ultrasonic wave application time increased. It was also confirmed that the viscosity rapidly decreased within 1 to 2 seconds, which is the initial time when the ultrasonic wave application started, and the viscosity converged to about 3 cP after 10 minutes.
[0104] Experimental Example 3: Measurement of molecular weight change before and after ultrasonic application Molecular weight is 1.2 x 10 6 g / mol of sodium hyaluronate (0.02 g) was placed in a graduated cylinder, and 0.9% (w / v) NaCl was added and dissolved to make a total volume of 20 mL to prepare a sodium hyaluronate aqueous solution. 0.8 mL of the aqueous solution was taken, and 0.1 M Na2SO4 was added to make a solution with a total volume of 10 mL. Then, distilled water was added to the solution to dilute the concentration by 2 times, and a sample for analysis by High-Performance Liquid Chromatography (HPLC) was prepared.
[0105] The solution prepared in the same manner as in Example 5 was placed in an ultrasonic generator, and ultrasonic waves were applied to prepare an aqueous solution containing a polymeric hyaluronic acid structure. Using the aqueous solution prepared above, a sample for gel permeation chromatography (GPC) measurement was prepared.
[0106] For the concentration and molecular weight analysis of the HPLC analysis sample and GPC measurement sample, HPLC (e2695, waters) and GPC column (OHPak SB-802.5 HQ 8.0×300 mm, 6 um, Shodex) were used. 0.1 M sodium sulfate (Na2SO4) aqueous solution prepared by dissolving 14.2 g of sodium sulfate anhydrous (DAEJUNG) in 1 L of purified water was used as the mobile phase. The column temperature was maintained at 40° C., the oven temperature at 25° C., 100% 0.1 M sodium sulfate (Na2SO4) was added, and the sample was stabilized in the oven at a flow rate of 1.0 mL / min for 1 hour. The sample was then filtered with a syringe filter (PVDF, 0.2 μm, Φ 13 mm), and 20 μL was injected into the GPC column and analyzed at UV 210 nm wavelength for 16 minutes.
[0107] In FIG. 6, (a) is a diagram showing the molecular weight of sodium hyaluronate, which is a precursor of the structure according to the present invention, and (b) is a diagram showing the molecular weight of the polymeric hyaluronan structure according to the present invention.
[0108] It was confirmed that the molecular weight of the hyaluronic acid precursor of the structure according to the present invention and the molecular weight of the polymeric hyaluronic acid structure according to the present invention were almost the same with no change.
[0109] Experimental Example 4: Preparation of viscosity-controlled solutions In the above-mentioned Example 5, the aqueous solution of hyaluronic acid sodium salt, which is the precursor, was subjected to ultrasonic waves at 25°C for 16 minutes using an ultrasonic homogenizer to prepare an aqueous solution (a) containing a structure of high molecular weight hyaluronic acid. In addition, the aqueous solution of hyaluronic acid sodium salt (b) to which ultrasonic waves were not applied was prepared, and mixed with the aqueous solution (a) to prepare a solution.
[0110] The viscosities of the solutions obtained by mixing the aqueous solutions (a) and (b) were compared and shown in Table 4 below.
[0111] [Table 4]
[0112] The results in Table 4 show that when the aqueous solution (a) containing the polymeric hyaluronic acid structure according to the present invention is mixed with the aqueous solution (b) that has not been subjected to ultrasonic treatment at about 10%, a solution having a viscosity of 3 to 6 cP can be produced.
[0113] Experimental Example 5: Preparation of Viscosity-Adjusted Eye Drop Composition Molecular weight is 1.0 x 10 6 0.3 g of sodium hyaluronate (Shiseido Co., Ltd.) was placed in a measuring cylinder and distilled water was added to bring the total volume to 100 ml. The solution was stirred at 25°C until it became homogeneous, producing an aqueous solution of sodium hyaluronate with a concentration of 0.3% (w / v).
[0114] The prepared aqueous solution of sodium hyaluronate having a concentration of 0.3 (w / v) % was treated in the same manner as in Examples 1 to 5 to prepare an aqueous solution containing a polymeric hyaluronate structure.
[0115] Additives were added to the prepared aqueous solution containing the polymeric hyaluronic acid structure to prepare an eye drop composition containing an aqueous solution containing the polymeric hyaluronic acid structure as shown in Table 5. The viscosity and osmotic pressure of the prepared eye drop composition were measured and are shown in Table 5.
[0116] [Table 5]
[0117] In Table 5, the vehicle used was one or more of phosphate-buffered saline (PBS), sodium chloride (NaCl), and additives, which included a mixture of 0.01% ethylenediaminetetraacetic acid disodium salt (EDTA-2Na), 0.19% aminocaproic acid, 0.69% sodium chloride (NaCl), 0.15% potassium chloride (KCl), and distilled water.
[0118] From the results in Table 5, it was confirmed that an eye drop composition having a viscosity in the range of 1 to 30 cP can be provided by adding various excipients to the aqueous solution containing the polymeric hyaluronic acid structure according to the present invention.
[0119] Experimental Example 6: Evaluation of water retention of aqueous solutions of Examples 1, 3, 5 and Comparative Example 1 The water retention capacity of the aqueous solutions of Examples 1, 3, and 5 and Comparative Example 1 was measured and evaluated. 1 g of each sample was taken and placed in a 10 cc vial and left at 25° C. for 1 hour, after which the change in weight was measured. The results are shown in Table 6 below.
[0120] [Table 6]
[0121] In the results of Table 6, it was confirmed that the aqueous solution of sodium hyaluronate treated with high pressure disperser or ultrasonic homogenizer has a lower viscosity than the aqueous solution of pure sodium hyaluronate (Comparative Example 1), but has a smaller weight change.Therefore, it was found that the aqueous solution containing the hyaluronate structure according to the present invention has a lower viscosity and is excellent in water retention.This result shows that it is suitable for use in artificial tears and the like that are required to improve water retention.
[0122] Experimental Example 7: Measurement of contact angles of aqueous solutions of Examples 1, 3, 5 and Comparative Example 1 The contact angles were measured for the aqueous solutions prepared in Examples 1, 3, and 5 and Comparative Example 1. The contact angles were measured on a hydrophilic glass surface and a hydrophobic glass surface, respectively. The measured contact angles are shown in Table 7 below.
[0123] [Table 7]
[0124] As can be seen from the results in Table 7, the contact angles of the aqueous solutions prepared in Examples 1, 3 and 5 on the hydrophilic glass surface were larger than that of Comparative Example 1, whereas the contact angles of the aqueous solutions prepared in Examples 1, 3 and 5 on the hydrophobic glass surface were smaller than that of Comparative Example 1. This indicates that the aqueous solutions prepared in Examples 1, 3 and 5 are relatively lipophilic.
[0125] Experimental Example 8: Intrinsic Viscosity Experiment The method for measuring intrinsic viscosity is to measure the aqueous solution to be measured according to the concentration, calculate the reduced viscosity, and extrapolate this to read the reduced viscosity at a concentration of 0, which is called the intrinsic viscosity. As mentioned above, the intrinsic viscosity refers to the volume per unit mass of the polymer when there is no interaction between polymer chains in the solvent.
[0126] The 0.5 (w / v)% aqueous solution of hyaluronic acid sodium salt prepared is diluted with distilled water to concentrations of 0.3 (w / v), 0.1 (w / v), 0.05 (w / v), 0.01 (w / v), and 0.005 (w / v). The viscosity is measured at 25°C using a Brookfield viscometer DV2T, which is calculated as the reduced viscosity and extrapolated to obtain the intrinsic viscosity. In the case of hyaluronic acid sodium salt having a molecular weight of 1.2 million, the viscosity is 2.3 m 3 In the case of sodium hyaluronic acid having an intrinsic viscosity of 1.8 m / kg and a molecular weight of 900,000, 3 / kg.
[0127] The aqueous solution containing the hyaluronic acid structure having a molecular weight of 900,000 prepared in Example 5 was about 0.8 ml 3 The intrinsic viscosity was calculated to be 1.0 g / kg.
Claims
1. It is a structure derived from high molecular weight hyaluronic acid, A polymeric hyaluronic acid structure, characterized in that a solution containing the structure has a viscosity of 1 to 60 cP.
2. The molecular weight of the hyaluronic acid is 5.0×10 5 ~2.0×10 6 The polymeric hyaluronic acid structure according to claim 1, characterized in that its molecular weight is in the range of g / mol.
3. The polymeric hyaluronic acid structure according to claim 1, wherein the solution containing the structure contains 0.01% (w / v) to 0.5% (w / v) of hyaluronic acid.
4. When the molecular weight and concentration of the structure and the hyaluronic acid precursor of the structure are the same, The polymeric hyaluronic acid structure according to claim 1, characterized in that the ratio of viscosity (a) of a solution containing the structure to viscosity (b) of a solution containing hyaluronic acid, which is a precursor of the structure, a / b, is 0.001 to 0.
30.
5. The intrinsic viscosity of the solution containing the structure is 0.1 to 2.5 m 3 2. The polymeric hyaluronic acid structure according to claim 1, wherein the polymeric hyaluronic acid structure has a molecular weight of 1000 to 15000 / kg.
6. An eye drop composition comprising the polymeric hyaluronic acid structure according to claim 1.
7. 7. The eye drop composition according to claim 6, wherein the viscosity of the eye drop composition is 1.0 to 30.0 cP.
8. The eye drop composition according to claim 6, further comprising an excipient.
9. 9. The ophthalmic composition according to claim 8, wherein the excipient is at least one selected from the group consisting of a buffer, a preservative, a tonicity adjusting agent, and a pH adjusting agent.
10. The eye drop composition according to any one of claims 6 to 9, which is for preventing or treating dry eye.
11. A kit comprising a container containing the eye drop composition according to any one of claims 6 to 9, The container comprises a dispensing means suitable for topical administration of the ophthalmic composition.
12. 12. The kit of claim 11, wherein the dispensing means provides the eye drop composition dropwise in a volume of 0.01 to 0.10 ml.
Citation Information
Patent Citations
Production of hyaluronic acid having high viscosity
JP1985024194A
The low molecular weight hyaluronic acid
JP1992505774A
Water-degradable films comprising hyaluronic acid or salt thereof and polyphenol compounds
JP2021042194A
Composition for treating meniscus degeneration
WO2017119198A1
KR2021-0015377